2018
DOI: 10.1039/c7ta11208d
|View full text |Cite
|
Sign up to set email alerts
|

An easily synthesized microporous framework material for the selective capture of radioactive Cs+ and Sr2+ ions

Abstract: FJSM-InMOF with facile synthesis showed remarkable Cs+ and Sr2+ ion-exchange performance with an unprecedented structural-transformation to illuminate the capture mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(43 citation statements)
references
References 59 publications
2
41
0
Order By: Relevance
“…Metal-organic frameworks (MOFs) are a novel class of crystallized porous materials that are self-assembled by metal clusters as connecting points and organic ligands as bridging molecules to form a two- or three-dimensional framework through coordination bonds [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. MOFs have attracted great interests in recent years by having remarkable features such as adjustable structure, high porosity, large specific surface area, good modifiability and excellent stability and have been used widely in many areas, for example, adsorption [ 8 , 9 , 10 , 11 , 12 , 13 ], catalysis [ 14 , 15 , 16 , 17 , 18 ], sensing [ 19 , 20 , 21 , 22 , 23 ], drug delivery [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and gas storage and separation [ 31 , 32 , 33 ], etc. Besides the intrinsic properties of MOFs, their morphology and size also play crucial roles for their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Metal-organic frameworks (MOFs) are a novel class of crystallized porous materials that are self-assembled by metal clusters as connecting points and organic ligands as bridging molecules to form a two- or three-dimensional framework through coordination bonds [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. MOFs have attracted great interests in recent years by having remarkable features such as adjustable structure, high porosity, large specific surface area, good modifiability and excellent stability and have been used widely in many areas, for example, adsorption [ 8 , 9 , 10 , 11 , 12 , 13 ], catalysis [ 14 , 15 , 16 , 17 , 18 ], sensing [ 19 , 20 , 21 , 22 , 23 ], drug delivery [ 24 , 25 , 26 , 27 , 28 , 29 , 30 ] and gas storage and separation [ 31 , 32 , 33 ], etc. Besides the intrinsic properties of MOFs, their morphology and size also play crucial roles for their practical applications.…”
Section: Introductionmentioning
confidence: 99%
“…The Cs + exchanged products exhibit evident characteristic peaks of 3d 5/2 and 3d 3/2 for Cs + at 724.5 and 738.6 eV ( Figures 3 c and d) for 1 , respectively, and at 724.7 and 738.6 eV ( Figures 3 e and f) for 2 in the XPS survey spectra. 45 The peaks at 399.3 and 402.1 eV can be assigned to N 1s of the amino groups 46 and dimethylamine cations in 1 , 29 respectively ( Figure S11a ). Contrasted with the pristine 1 and 2 , the characteristic peaks for N 1s of the dimethylamine cation for 1-Cs and 2-Cs at 402.1 and 402.3 eV, respectively, almost disappear ( Figure S11 ).…”
Section: Resultsmentioning
confidence: 99%
“… 28 Our group reported the 3D FJSM-In MOF with an excellent radiation stability, a high removal rate, and a high selectivity for Cs + . 29 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Investigation of iodine adsorption on both un‐ and irradiated samples showed that the adsorbing capacity is not significantly affected by 200 kGy β irradiation (Figure S4), further supporting the radiation resistance of 1 . As far as we know, only a few stable MOFs with radiation resistance ability was explored under less than 2×10 5 Gy β irradiation (Table S9), whereas the investigations on stability of MOFs under 4×10 5 Gy β irradiation have not been reported so far.…”
Section: Figurementioning
confidence: 99%